ANALISIS RASIO KEUANGAN TERHADAP KINERJA BANK SYARIAH INDONESIA PASCA MERGER - Puspita Ningrum, Ratih; Alan Nur, Muhammad; Sukardi, Budi (Jurnal Ekonomika dan Bisnis Islam, 2023)
Financial performance describes an achievement over a certain period of time on the procedures for managing a bank's finances. This research aims to measure how the performance of Indonesian Sharia Banks in 2022 so that it can be ranked as the 6th largest bank in Indonesia. Descriptive research method using financial ratio analysis, the ratio used is the ratio of liquidity, profitability, and solvency. The results in this study indicate that the FDR ratio of Indonesian Sharia Banks performs in a poor category, because it does not meet BI regulatory standards. While the cash ratio, ROA, ROE, BOPO, and CAR are in good condition, because these ratios comply with BI regulations. The implications of this research for readers can be used as a reference for writing further scientific papers. Meanwhile, companies, especially Bank Syariah Indonesia, are expected to improve their financial performance so they can improve their performance in 2023.